A Application of The Approach To Game Obstacles Material Stands Away Style Students Class IX A SMP Negeri 5 Kendari - Wati Wati (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2020)
The purpose of this study is to improve the ability of students of class IX A SMP Negeri 5 Kendari in doing squat style long jump practicum through obstacle games. This research uses action research as much as three rounds. Each round consists of two stages: planning, implementing, observing, and reflecting. From the results of the analysis, it was found that increasing the quality of long jump squat style with an obstacle course in the first cycle with a total value of 2155, an average of 67.34, the highest value of 80 and the lowest 55. In the second cycle with a total value of 2280, an average of 71, 25, the highest value is 85 and the lowest is 60 and has increased in cycle III with a total value of 2465, an average of 77.03, the highest value of 90 and the lowest 70. The conclusion of this study is the obstacle course can positively influence the ability of students of grade IX-A SMP Negeri 5 Kendari to do the squat-style long jump.